DEVELOPING DIGITAL AND INNOVATION COMPETENCE OF TEACHERS THROUGH THE USE OF ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN HIGHER EDUCATIONAL INSTITUTIONS - Hakimova Nargiza Suphonovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Abstract, this article analyzes the theoretical foundations, practical aspects and methodological approaches to developing digital and innovative competence of teachers through the use of artificial intelligence technologies in higher education institutions. Models of integration of SI technologies into pedagogical activities, stages of competence development, as well as issues of psychological and technological readiness of professors and teachers for digital transformation are covered. The author proposes a systematic approach aimed at increasing the digital competence of pedagogical staff in higher education.